2008
DOI: 10.1002/chem.200701780
|View full text |Cite
|
Sign up to set email alerts
|

High‐Throughput Kinetic Study of Hydrogenation over Palladium Nanoparticles: Combination of Reaction and Analysis

Abstract: The hydrogenation of 1-acetylcyclohexene, cyclohex-2-enone, nitrobenzene, and trans-methylpent-3-enoate catalyzed by highly active palladium nanoparticles was studied by high-throughput on-column reaction gas chromatography. In these experiments, catalysis and separation of educts and products is integrated by the use of a catalytically active gas chromatographic stationary phase, which allows reaction rate measurements to be efficiently performed by employing reactant libraries. Palladium nanoparticles embedd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
50
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 92 publications
1
50
0
1
Order By: Relevance
“…Elemental analyses indicated that the Pd/L ratio found on the isolated PdNPs was: Pd/L1 = 1/0.27 and Pd/L2 = 1/0.50 (corresponding to a ratio Pd/L at the surface PdL10. 4 and PdL20.8). Concerning RuNPs, small nanoparticles were also obtained, with a mean diameter of 1.0 and 1.2 nm for RuL1 and RuL2, respectively.…”
Section: Synthesis and Characterisation Of Pdnps And Runpsmentioning
confidence: 95%
See 3 more Smart Citations
“…Elemental analyses indicated that the Pd/L ratio found on the isolated PdNPs was: Pd/L1 = 1/0.27 and Pd/L2 = 1/0.50 (corresponding to a ratio Pd/L at the surface PdL10. 4 and PdL20.8). Concerning RuNPs, small nanoparticles were also obtained, with a mean diameter of 1.0 and 1.2 nm for RuL1 and RuL2, respectively.…”
Section: Synthesis and Characterisation Of Pdnps And Runpsmentioning
confidence: 95%
“…Elemental analyses indicated that the Ru/L ratio found on the isolated RuNPs was: Ru/L1 = 1/0.56 and Ru/L2 = 1/0.46 (corresponding to a ratio Pd/L at the surface PdL10. 4 and PdL20.8).…”
Section: Synthesis and Characterisation Of Pdnps And Runpsmentioning
confidence: 95%
See 2 more Smart Citations
“…These catalytic systemsw ere recently characterized in detail in our studies. [13,17,18] We reported the high activity of the Ru nanoparticles in combination with ap ronounced CO chemoselectivity.H igh turnover numbers( TONs) of up to 60 000 correlated well with more than 200 catalytic cycles corresponding to ar eaction time of about 5s.[13] Therefore, we assumethat Ru nanoparticle catalysts should provide the selective conversion of 1.S imultaneously,P di sw ell known as highlya ctive catalysti nt he total hydrogenation of furfural derivatives. [4,5,8] Ru andPdnanoparticles were prepared by the previously established method.…”
mentioning
confidence: 94%